Supply Chain Analysis of Beef from Slaughterhouse to End Consumers (Case Study: Bangkong Slaughterhouse) - Irwansyah Irwansyah; Samuyus Nealma; Sudirman Sudirman; Sukarne Sukarne (Jurnal Biologi Tropis, 2022)
Livestock is a sector that has a huge opportunity to be developed as a business in the future. According to BPS data in 2014 there were 4.104 heads of cattle and in 2016 decreased with a total of slaughtering as many as 3,461 heads of cattle. From this data it can be seen that the number of cattle slaughtering in Sumbawa Regency can be said to be quite low for the needs of beef in Sumbawa Regency. In Sumbawa especially, the problem of beef lies in relatively expensive price. This study aims to determine the supply chain of beef from slaughterhouse to end consumers by using data collection methods, and determining respondents (snowball sampling technique and purposive sampling technique). The result of this study is the marketing efficiency of beef shows that the efficiency of marketing of 0 (zero) level of beef seller-consumer is 0% smaller compared to the level marketing efficiency of level 1 (one) of meat retailers-consumers of 0.87 %. Value added at the level of beef seller (butcher) shows that the conversion factor value is 1.30 where the conversion factor is obtained by dividing the output value with the input value for every 1 medium-sized cattle.